Inventarisasi Karakteristik Mataair Di Sebagian Lereng Selatan Gunungapi Slamet Kabupaten Banyumas Melalui Pendekatan Penginderaan Jauh - Ibrahim, Farid, Drs. Yuli Priyana, M.Si, Agus Anggoro Sigit, S.Si, M.Sc (2015)
The presence of spring is influenced by land physical factors which are gradient of slope, rock formation, landcover and also spring-belt. They are can be intrepreted through remote sensing and geographical information system approach which able to showing the patterns and identical appeareance of land units. The goals of of this research that are: 1). to analyze the characteristic of spring on southern part of Slamet Volcano based on phisical land parameter, 2). to mapping the potency of spring presence on southern part of Slamet Volcano through remote sensing and geographical information system approach. Research method which is used in this study by surveying for accuracy of interpretation result. Analysis method is overlaying the interpretation resulted maps to obtain land units that indicate the presence of spring. The result of these land units subsequently taken as sample to be tested for the accuracy by using stratified purposive sampling technique where the land units as the stratum. This will show the the zonation of spring presence when overlaying to straight pattern as the spring main indicator. The technique of remote sensing and geographical information system are used for collecting data and processing of spatial data. The results of this research which are showing the very potencial spring resources of southern slope of Slamet Volcano with 4 types of presence: a). the potencial volcanic spring can be idetified through the changing of volcanic sub-morphology interpretation, b). the depression of spring which is known from the closed-contour pattern, c). the contact spring that is known from the presence of tributary to denudational hill-sides, and d). the split spring which is known from the changing of landuse by dried to moisted emphatically. Keywords : spring, remote sensing, geographical information system, overlay, land units